ENT 530 Social Media Report: Café Kita / Puteri Hanani Osman - Osman, Puteri Hanani (2021)
Café Kita is about my love for coffee, design, and seeing the world. Cafe Kita prides themselves on providing prime quality coffee with unique taste profiles. Besides, Café Kita can also offer some other important health benefits and nutritions. Café Kita have been in business for over 2 years now, they continue to supply the best instant health coffee by producing ‘Maca’ for men and ‘Pearl’ for women. Other than green coffee bean that help lose weight, Maca coffee contain Tongkat Ali that boost athletic performance and increase muscle mass. Theres so many other benefits contain in Café Kita coffee. Their coffee has richness that comes from freshly instant roasted coffee. The art of crafting the best tasting coffee requires respecting each individual roast. Knowing the specific origin and roast degree for each coffee allows for intense flavor that can be traced back to its earliest beginnings. Our high standards make their coffee uniquely and uniformly delicious.